Genome-wide SNP Associations with Rubella-Specific Cytokine Responses in Measles-Mumps-Rubella Vaccine Recipients - Kennedy, Richard B. (2014)
Genetic polymorphisms are known to affect responses to both viral infection and vaccination. Our previous work has described genetic polymorphisms significantly associated with variations in immune response to rubella vaccine from multiple gene families with known immune function, including: HLA, cytokine and cytokine receptor genes, and in genes controlling innate and adaptive immunity. In this study, we assessed cellular immune responses (IFNγ and IL-6) in a cohort of healthy younger individuals and performed genome wide SNP analysis on these same individuals. Here, we report the first genome-wide association study focused on immune responses following rubella vaccination. Our results indicate that rs16928280 in PTPRD (protein tyrosine phosphatase delta) and a collection of SNPs in ACO1 (encoding an iron regulatory protein) are associated with inter-individual variations in IFNγ response to rubella virus stimulation. In contrast, we did not identify any significant genetic associations with rubella-specific IL-6 response. These genetic regions may influence rubella vaccine-induced IFNγ responses and warrant further studies in additional cohorts in order to confirm these findings.